Influence of nitrogen protection on the extraction yield and antioxidant activities of polyphenols by ultrasonic‐assisted extraction from rapeseed meal. (30th May 2019) - Ding, Qingzhi; Jiang, Hanfei; Chen, Yuxin; Luo, Lin; He, Ronghai; Ma, Haile; Wu‐Chen, Ricardo A.; Zhang, Ting
Abstract: It has been found that ultrasonic‐assisted extraction (UAE) can dramatically increase extraction yield of polyphenols from raw materials. However, the free radical formation induced by ultrasound will cause a series of oxidation reactions, which may reduce the antioxidant activities of polyphenols. To minimize the oxidation effect produced by ultrasound and increase the biological activities of polyphenols, ultrasonic‐assisted nitrogen‐protected extraction (UANPE) was employed to extract polyphenols from rapeseed meal. Experimental results obtained by iodine release test and electron paramagnetic resonance analyses demonstrated that the oxidation reaction and the quantity of free radicals are significantly less ( p  < .05) in the UANPE process than those in the UAE process without nitrogen protection. According to the single‐factor optimization results, the highest yield of rapeseed polyphenols (RPs) of 12.64 mg/g by UANPE was achieved under the optimal extraction conditions of the material/liquid of 1:30 (g/mL), the ultrasonic extraction time of 30 min, the extraction power of 240 W, and the nitrogen flow rate of 5 L/min. Moreover, the RPs extracted by UANPE exhibited higher antioxidant abilities and inhibition effects on the growth of cancer cells. These results substantiated that UANPE may be an innovative and efficient method in the field of bioactive compounds extraction. Practical applications: Ultrasonic‐assisted extraction (UAE) is an efficient extraction method. It has been widely used to intensify the extraction of active substances from natural products. However, the free radicals produced by ultrasound will reduce the biological activities of the extract. In order to overcome this obstacle, the nitrogen protection (NP) was used to inhibit the production of free radicals and reduce their oxidation reaction during UAE. Then, the iodine release and electron paramagnetic resonance were determined to evaluate the effect of NP on inhibiting the formation of free radicals induced by ultrasound. Finally, to evaluate its practical value on the extraction effect, a novel method called the ultrasonic‐assisted nitrogen‐protected extraction was used for polyphenols extraction from rapeseed meal. According to the experimental results, this method can not only increase the extraction yield, but also maintain the high antioxidant activities of rapeseed polyphenols.